Knowledge discovery practices and emerging applications of data mining : trends and new domains - Senthil kumar, A., 1966- (Hershey, Pa. : Information Science Reference, 2011)
'This book introduces the reader to recent research activities in the field of data mining, covering association mining, classification, mobile marketing, opinion mining, microarray data mining, internet mining and applications of data mining on biological data, telecommunication and distributed databases'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Data mining; Knowledge acquisition (Expert systems)